2007
DOI: 10.1111/j.1533-2500.2007.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Malingering in Contested Injury or Illness

Abstract: An interdisciplinary task force of physicians and neuropsychologists with advanced training in impairment and disability assessment provided a review of the literature on malingering in chronic pain, medical disorders, and mental/cognitive disorders. Our review suggests that treating health care providers often do not consider malingering, even in cases of delayed recovery involving work injuries or other personal injuries, where there may be a significant incentive to feign or embellish symptoms or delay reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 121 publications
0
25
0
4
Order By: Relevance
“…Further independent research should examine whether this statement extends to all levels of severity. Considering the results, it is recommended that the TOMM be used in conjunction with evidence gathered from other sources as recommended by Aronoff et al (2007) and Tombaugh (1996). Failure to do so could lead to serious unintended consequences for an individual's compensation, rehabilitation, and entitlement to benefits.…”
mentioning
confidence: 99%
“…Further independent research should examine whether this statement extends to all levels of severity. Considering the results, it is recommended that the TOMM be used in conjunction with evidence gathered from other sources as recommended by Aronoff et al (2007) and Tombaugh (1996). Failure to do so could lead to serious unintended consequences for an individual's compensation, rehabilitation, and entitlement to benefits.…”
mentioning
confidence: 99%
“…In our study, the two individual probabilistic indices showed a small to moderate increase in the likelihood of having detected a simulator if positive (above the cutoff point) and a moderate to large decrease in the likelihood of not having detected a simulator if negative (below the cutoff point). The SCL-90-R could then be applied as a brief screening previous to the thorough assessment and the consideration of multiple sources of converging data needed before concluding that a person is malingering an illness (Aronoff et al, 2007). However, in taking into account the above-mentioned magnitude of the likelihood ratios, it seems more prudent to interpret the individual probabilistic indices as a suggestion to rule out the simulation rather than to detect a simulator.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, the assessment of the possibility of deception has been recommended during the assessment of pain (Hill & Craig, 2004;Iverson, 2007), with special emphasis in litigant claimants scenarios, in which a 30% to 40% incidence of malingering has been suggested (Aronoff et al, 2007). In our study, the two individual probabilistic indices showed a small to moderate increase in the likelihood of having detected a simulator if positive (above the cutoff point) and a moderate to large decrease in the likelihood of not having detected a simulator if negative (below the cutoff point).…”
Section: Discussionmentioning
confidence: 99%
“…This Stage is analogous to the sick role as discussed in the general biopsychosocial model above (Engel, 1977). In addition to the focus on pain, the individual at this Stage exhibits poor social and occupational functioning, and begins to develop secondary gain issues (Aronoff et al, 2007;Dersh, Polatin, Leeman, & Gatchel, 2004;Fishbain, 1994;Leeman, Polatin, Gatchel, & Kishino, 2000). Such behaviors are characterized by the avoidance of responsibilities, and seeking out financial compensation for the pain.…”
Section: Development Of Pain: From Acute To Chronicmentioning
confidence: 98%